2015
DOI: 10.1007/s00330-015-3754-8
|View full text |Cite
|
Sign up to set email alerts
|

Survival Prognostic Value of Morphological and Metabolic variables in Patients with Stage I and II Non-Small Cell Lung Cancer

Abstract: • Identifying variables that predict the prognosis of patients with NSCLC is important. • SUVmax in primary lung tumour is a useful independent prognostic variable. • (CTvol) is an independent prognostic variable if no lymph nodes are involved.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 13 publications
2
23
1
Order By: Relevance
“…Volumetric parameters have gained increasingly interest as prognostic factors for various cancers [18]. However, to date, only few studies have focused on MTV repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…Volumetric parameters have gained increasingly interest as prognostic factors for various cancers [18]. However, to date, only few studies have focused on MTV repeatability.…”
Section: Discussionmentioning
confidence: 99%
“…Quantitative methods to measure tumor heterogeneity have been shown to play a role in the assessment of cancer response to therapy101112. Intratumor heterogeneity measured by texture parameters on non-enhanced and/or contrast material-enhanced CT images between baseline and initial post-therapy have been associated with overall survival (OS) in patients with colorectal cancer13, metastatic renal cell cancer14, esophageal cancer15, and NSCLC16171819.…”
mentioning
confidence: 99%
“…Herein, both MTV and TLG can better reflect the metabolic activity of the whole tumor, whereas SUVmax only represents information of a single pixel. Recent publications have reported that higher MTV and higher TLG showed a significant association with worse overall survival or disease‐free survival in patients with node‐negative NSCLC . Additionally, in a report by Shiono, the SUV index (a ratio of primary tumor SUVmax to liver SUV mean) was a significant prognostic indicator for stage IA NSCLC.…”
Section: Introductionmentioning
confidence: 92%
“…As shown in Table 2, there are 11 available reports that analyzed the prognostic significance of FDG accumulation in resected node-negative NSCLC. [43][44][45][46][47][48][49][50][51][52][53] All reports, except for two, included pathological stage IB NSCLC. 43,44 All of the examined studies reported the significant association between FDG accumulation and prognosis in patients with clinically node-negative NSCLC.…”
Section: Primary Tumor Fdg Accumulation As a Prognosticatormentioning
confidence: 99%
See 1 more Smart Citation